The genus Psyttalia Walker (Hymenoptera, Braconidae) in Vietnam: descriptions of seven new species and their host information - Oanh, Nguyen Thi; Long, Khuat Dang; Xuan, Trinh Thi; Tinh, Duong Van; Nghiep, Hoang Thi (Zootaxa, 2024)
The genus Psyttalia Walker is recorded for the first time from Vietnam with seven species described and fully illustrated as new for science, viz. Psyttalia antenervis Long, sp. nov., P. hoabinhensis Long, sp. nov., P. mangiferae Long & Oanh, sp. nov., P. nigristriata Long, sp. nov., P. quadrinervis Long, sp. nov., P. sonla Long, sp. nov. and P. tricolorata Long, sp. nov. Two species, P. incisi (Silvestri) and P. latinervis Wu & van Achterberg, are newly recorded for Vietnam’s braconid fauna. Additionally, the diagnosis of a putative female of P. latinervis is given. Host records are provided for P. mangiferae, sp. nov., which is mainly reared from tephritid larvae of Oriental fruit fly, Bactrocera dorsalis, infesting fruits of mango, Mangifera indica, in South Vietnam. A key to Vietnamese Psyttalia species is provided, and comparative morphological characters of Psyttalia species are discussed.